If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p = 2p + -4qforp Reorder the terms: 5p = -4fopqr + 2p Solving 5p = -4fopqr + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4fopqr' to each side of the equation. 4fopqr + 5p = -4fopqr + 4fopqr + 2p Combine like terms: -4fopqr + 4fopqr = 0 4fopqr + 5p = 0 + 2p 4fopqr + 5p = 2p Add '-2p' to each side of the equation. 4fopqr + 5p + -2p = 2p + -2p Combine like terms: 5p + -2p = 3p 4fopqr + 3p = 2p + -2p Combine like terms: 2p + -2p = 0 4fopqr + 3p = 0 Factor out the Greatest Common Factor (GCF), 'p'. p(4foqr + 3) = 0Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(4foqr + 3)' equal to zero and attempt to solve: Simplifying 4foqr + 3 = 0 Reorder the terms: 3 + 4foqr = 0 Solving 3 + 4foqr = 0 Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4foqr = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4foqr = 0 + -3 4foqr = 0 + -3 Combine like terms: 0 + -3 = -3 4foqr = -3 Add '-4foqr' to each side of the equation. 4foqr + -4foqr = -3 + -4foqr Combine like terms: 4foqr + -4foqr = 0 0 = -3 + -4foqr Simplifying 0 = -3 + -4foqr The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
p = {0}
| -1.80=4.9x-4.9(x^2) | | -4=-5+x | | -2m+(-6m)= | | 10x-1=9x+8 | | 8(y+3)=4Y+32 | | 4x+(-3x)= | | -16-5z=51 | | 8(7+3)=4y+32 | | (x-8x-20)=(x+2) | | 2.22-3.34x=2x-4.555 | | 5y+3-2y-1=25 | | 3x+7=-8x+2 | | 58x^2+40x=0 | | 1.2x=1.4 | | 6-2x=-5x-9+14 | | 24m-16n= | | a+(a-9)=(a-7)-(a+2) | | (X+9x+18)=(x+6) | | 8x-22=230-10x | | 11=-2 | | -2and-38=76 | | 24+8*x=3*x-4 | | -88=-8(1-3r) | | 3(x+5)-10=2(x+1) | | 3p+5=9p-7 | | 15=-p-2 | | 4-2k=-5k+35 | | 49=-7d | | (m+12)+2m+90=180 | | W*5+17=-3 | | (x+3)-2(2-4x)=3(x+4)-1 | | 5x+(x+24)=180 |